2014
DOI: 10.1104/pp.114.243766
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nitrate Transporter 1.1-Controlled Nitrate Uptake Reduces Cadmium Uptake in Arabidopsis

Abstract: Identification of mechanisms that decrease cadmium accumulation in plants is a prerequisite for minimizing dietary uptake of cadmium from contaminated crops. Here, we show that cadmium inhibits nitrate transporter 1.1 (NRT1.1)-mediated nitrate (NO 3 2 ) uptake in Arabidopsis (Arabidopsis thaliana) and impairs NO 3 2 homeostasis in roots. In NO 3 2-containing medium, loss of NRT1.1 function in nrt1.1 mutants leads to decreased levels of cadmium and several other metals in both roots and shoots and results in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 44 publications
5
61
0
1
Order By: Relevance
“…A disruption in NRT1.1 affects the expression of other NRT genes [10,24,31,32], which is highly associated with growth conditions. A critical factor in the controversial conclusions described above may be the variable interference resulting from nitrate uptake by other NRTs.…”
Section: Nitrate (No àmentioning
confidence: 99%
“…A disruption in NRT1.1 affects the expression of other NRT genes [10,24,31,32], which is highly associated with growth conditions. A critical factor in the controversial conclusions described above may be the variable interference resulting from nitrate uptake by other NRTs.…”
Section: Nitrate (No àmentioning
confidence: 99%
“…Crops grown in Cd‐contaminated soils are the main route of Cd entry into the human body through the food chain, causing a serious threat to human health (Clemens, Aarts, Thomine, & Verbruggen, ; Wei & Yang, ). Excess Cd accumulation in plants also causes several visible phytotoxic symptoms, including retardation of growth, modification of enzymes, chlorosis of the leaf, oxidative stress, and disturbances in mineral nutrition (Choppala et al, ; Lux, Martinka, Vaculik, & White, ; Mao et al, ). To cope with these adverse effects, plants have evolved a host of protective mechanisms to minimize Cd toxicity, such as prevention of Cd entry into the roots, compartmentalization of Cd in vacuoles, Cd chelation by phytochelatins and metallothioneins, and immobilization of Cd in the cell wall (Choppala et al, ; Clemens et al, ; Guan, Zhang, Pan, Jin, & Lin, ; Lux et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Histochemical assay of GUS gene expression in roots of DR5::GUS transgenic plants was performed as described in our previous study (Mao et al, 2014), and the distribution and intensity of the blue product observed under a microscope (Nikon Eclipse E600, Nikon).…”
Section: Chlorophyll Quantification and Gus Staining Assaymentioning
confidence: 99%